2017
DOI: 10.7753/ijcatr0601.1005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Information and Communication Technology-induced Multitasking on Academic Performance of University Students in Uganda

Abstract: Numerous researches on information and communication technology (ICT)-induced multitasking among students document a number of unfavourable consequences, such as heightened distraction and less attention, hampered learning and hindered productivity at the expense of better academic performance. This study focused on the effect of information and communication technology induced multitasking on academic performance of university students in Uganda. To this end, primary data were collected during the month of Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…In Uganda, Jehopio, Wesonga, and Candia (2017) conducted a study that focused on the impact of information and communication technology (ICT) induced multitasking on university students' academic performance. Results indicated that ICT-induced multitasking did not have direct impact on academic performance but was mediated by the participants' self-regulation, attention span, emotional control and productivity focus.…”
Section: Introductionmentioning
confidence: 99%
“…In Uganda, Jehopio, Wesonga, and Candia (2017) conducted a study that focused on the impact of information and communication technology (ICT) induced multitasking on university students' academic performance. Results indicated that ICT-induced multitasking did not have direct impact on academic performance but was mediated by the participants' self-regulation, attention span, emotional control and productivity focus.…”
Section: Introductionmentioning
confidence: 99%
“…Alatawi [2016], Jehopio et al [2017], Dion [2016], Paul et al [2012] and Liu et al [2017] stated that Instagram affects the academic performance of students either positively or negatively. Students could use Instagram to communicate with peers about assignments or searching for references.…”
Section: Introductionmentioning
confidence: 99%